Survey of the Thermodynamic Properties of the Charge Density Wave Systems - M. Saint-Paul; P. Monceau (Advances in Condensed Matter Physics)
We reexamine the thermodynamic properties such as specific heat, thermal expansion, and elastic constants at the charge density wave (CDW) phase transition in several one- and two-dimensional materials. The amplitude of the specific heat anomaly at the CDW phase transition TCDW increases with increasing TCDW and a tendency to a lineal temperature dependence is verified. The Ehrenfest mean field theory relationships are approximately satisfied by several compounds such as the rare earth tritelluride compound TbTe3, transition metal dichalcogenide compound 2H-NbSe2, and quasi-one-dimensional conductor K0.3MoO3. In contrast inconsistency exists in the Ehrenfest relationships with the transition metal dichalcogenide compounds 2H-TaSe2 and TiSe2 having a different thermodynamic behavior at the transition temperature TCDW. It seems that elastic properties in the ordered phase of most of the compounds are related to the temperature dependence of the order parameter which follows a BCS behavior.